Safety-involved co-optimization of speed trajectory and energy management for fuel cell-battery electric vehicle in car-following scenarios - Longlong Zhu; Fazhan Tao; Zhumu Fu; Mengyang Li; Guoqu Deng (Complex & Intelligent Systems)
Abstract Vehicle connectivity technologies has propelled integrated optimization of vehicle’s motion and power splitting becoming a hotspot in eco-driving control research. However, the security issues and power sources life loss of fuel cell-battery hybrid electric vehicle (FCHEV) are still challenging due to disturbances and power sources degradation. To address these problems, in this paper, control barrier function (CBF) based multi-objective energy management strategy (EMS) for FCHEV in car-following process is proposed. Firstly, the state of health models of fuel cell and battery are established to reflect the relationship between power sources degradation and energy consumption. Secondly, multi-objective model predictive control (MPC) based EMS framework is developed by comprehensive considering tracking performance, comfort, fuel consumption and power sources life loss. Thirdly, to robustly cope with disturbances and uncertainties, discrete-time CBFs are designed to enforce safety-critical constraints related to safety issues of both vehicle dynamics and powertrain operation in MPC. Finally, comprehensive simulations in extreme and long driving cycle testing scenarios show the proposed strategy can prevent vehicles from entering unsafe states, while improving fuel economy by 9.95%, reducing power sources life loss by 6.53%.